(untitled) (Journal of Pharmaceutical Negative Results, 2022)
For almost two hundred years, diabetes mellitus has been a major health problem worldwide. While there has been progress in our knowledge of its pathophysiology and treatment, the therapeutic choices available today are woefully inadequate. The goal of transdermal medication delivery systems is to provide therapeutically effective doses of a medicine via the skin. The medicine is released at a steady, regulated pace thanks to the design of these devices. As a result, it is well suited for the management of long-term conditions like diabetes. Thus, the risks and inconvenient nature of the oral and parenteral routes are avoided. The purpose of this study is to develop and test eucalyptol transdermal patches for the treatment of diabetes. Drug distribution from different polymer-based transdermal patches might be enhanced by using oleic acid as a penetration enhancer. Matrix-style transdermal patches, composed of PVP K30, HPMC K100, and solvent, were created utilizing solvent casting procedures. By using Fourier transform infrared spectroscopy, researchers were able to examine the drug's and polymers' physicochemical compatibility. No evidence of physical or chemical incompatibility between the medication and the polymers was found. The patches also underwent a battery of physical tests in addition to the in-vivo research. The patches with the polymers, that is, PVP K30, HPMC K100, and oleic acid as the penetration enhancer, were regarded the best formulations for the transdermal distribution of eucalyptol based on the findings obtained from the physical assessment, ex vivo investigations, and in-vivo studies.